Arte, design e matemática: imagens, algorítimos e diversidade cultural - ROSA, Vanessa Gonçalves de Almeida (2019)
This dissertation discusses the issue of algorithms mainly from their characteristics as a representational model, in other words, tool to create images. It's an artist-oriented approach, how it is possible to express oneself through algorithms, but also designeroriented, how one can project with them. First, we try to understand the specificity of algorithmic images within the history of representation, why they mean a paradigm shift in relation to previous representational models, their place within the congruence of art history, or rather, history of images, with the history of science. Second, it is assumed that it is essential to discuss trends in imagery and technology development through an approach that focuses on cultural diversity, considering such approach a political necessity to comment and, as far as possible, to influence the changes that are occurring globally. Therefore, a combination of several fields of knowledge, articulated around concepts such as "representational models", "algorithms", "mathematization of the world" and "cultural diversity" are presented. The research is also based on empirical experience, narrated in the second section of the last chapter with a case study. This research hopes to contribute to the expansion of studies on design, algorithmic processes of image and object creation that are based on a broad and multicultural view of mathematics. This is an ethical and historical contribution to such studies.